Factors influencing implementation of mass drug administration for lymphatic filariasis elimination: a mixed-method study in Odisha, India - Ratna, P.; Sinha, Abhinav; Pati, Sanghamitra; Sahoo, Prakash Kumar (Frontiers in Pharmacology, 2024)
Background: Lymphatic filariasis (LF) persists as a public health problem in India. Despite more than ten rounds of mass drug administration (MDA), LF continues to be endemic in the Dhenkanal district of Odisha. Hence, we assessed the coverage and compliance of the MDA program and explored the factors affecting it in the Dhenkanal district. Methods: An explanatory mixed-method study was conducted, wherein for the quantitative survey, 552 participants aged 2 years and above were recruited following a multistage cluster random sampling during February 2022. In-depth interviews were conducted among purposively selected key stakeholders and program implementers. Descriptive statistics were used to report coverage and compliance, along with a 95% confidence interval. Qualitative data were analyzed using a thematic approach. Results: We observed coverage of 99.28% and compliance of 85.87% for MDA drugs. Supervised drug administration proved to be a major pillar in increasing compliance. There was difficulty in administering drugs in urban areas due to gated societies, the absence of individuals during the day, and the perspective toward healthcare providers. Participants reported a lack of confidence in drug distributors and a fear of side effects as major causes for non-compliance. Conclusion: There is a need to strengthen MDA, especially in urban areas. An urban-specific strategy, along with surveillance, behavioral change communication, and the involvement of multi-disciplinary teams, is required.